Dermatologic manifestations and neuropathic symptoms in women with Fabry disease - Melpignano, Andrea; Mandurino-Mirizzi, Alessandro; Besagni, Francesca; Leri, Annarosa (Acta Biomedica Atenei Parmensis, 2014)
Fabry disease (angiokeratoma corporis diffusum universale) is a rare, progressive, X-linked lysosomal storage disease. Deficiency of the α-galactosidase A (α-gal A) enzyme leads to accumulation of neutral glycosphingolipids within vascular endothelial lysosomes of various organs, including skin, kidneys, heart, and brain.1. We herein describe the case of a 30-year-old female presenting two classic signs of Fabry disease, angiokeratomas and episodic acroparesthesias, in the absence of other clinical manifestations. An haplotype corresponding to the combination of three different nucleotide polymorphic variants (g. 7192-7198del5+ g. 10115A>G + g. 10956 C>T) at the heterozygous state, was identified.2